2021
DOI: 10.3390/pathogens10070845
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for the Involvement of Leiomodin-1 Antibodies in the Pathogenesis of Onchocerciasis-Associated Epilepsy

Abstract: Nodding syndrome has been suggested to be triggered by neurotoxic leiomodin-1 auto-antibodies cross-reacting with Onchocerca volvulus. Here, we screened serum and CSF samples of persons with nodding syndrome and other forms of onchocerciasis-associated epilepsy (OAE) and African and European controls for leiomodin-1 antibodies by a cell-based assay (CBA) and Western blot (WB). These samples were also investigated for the presence of auto-antibodies cross-reacting with rat brain tissue by immunohistochemistry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“… 7 However, a subsequent study did not support the pathogenic role for leiomodin-1 autoantibodies in NS. 38 Our neuropathologic findings do not indicate how onchocerciasis could cause NS. But, serological studies of antibodies to Onchocerca volvulus were not available for our cases.…”
Section: Discussionmentioning
confidence: 57%
“… 7 However, a subsequent study did not support the pathogenic role for leiomodin-1 autoantibodies in NS. 38 Our neuropathologic findings do not indicate how onchocerciasis could cause NS. But, serological studies of antibodies to Onchocerca volvulus were not available for our cases.…”
Section: Discussionmentioning
confidence: 57%
“…Ov-associated antibodies (Hu-leiomodin-1 and Ov-16 IgG) were present in both participants with NS and OAE, with no statistically significant association between the level of antibodies and the degree of brain atrophy in either of the 2 groups. Although Hu-leiomodin-1 antibody is proposed to be a pathogenic immune mediator in NS by Johnson et al, 11,12 this association was not confirmed by Hotterbeekx et al 10 in a study with participants with OAE from DR Congo. There were significant differences in the methodology of these studies that could explain the difference in the findings.…”
Section: Discussionmentioning
confidence: 89%
“…[3][4][5] The parasite is also associated with other forms of epilepsy, known as onchocerciasisassociated epilepsy (OAE). [6][7][8][9] Although the results have been inconsistent, 10 parasite-driven antibody responses cross-reacting with human leiomodin-1 protein or other proteins have been proposed to underly the epileptogenesis in NS. 11 Leiomodin-1 protein is a member of the tropomodulin family and functions as an actin nucleating protein in smooth muscle cells, 12 but it is also expressed in the mouse hippocampus, cerebellar Purkinje cells, and cortical neurons and on the membranes of newly formed neurons and astrocytes.…”
mentioning
confidence: 99%
“…While the etiology of NS is unknown, the disease has affected infants and children of impoverished populations in which nematode infestation and food stress are significant factors, and in whom vitamin B6 levels are low. An autoimmune disorder is posited, but studies of cross-reactivity of OV and neuroproteins have yielded contradictory results [ 14 , 15 , 81 ], and OV antibody-negative NS cases are reported [ 82 ]. Displaced and food-insecure families used wild plants and mushrooms as emergency food.…”
Section: Discussionmentioning
confidence: 99%